Família, afeto e sucessão - Simões, Thiago Felipe Vargas (2007)
The Inheritance law has linking with all its too much areas. Its norms, as the Family law, is coated with public character. The familiar relations if modify not only for questions treated for the legislator, since from 1988 the family started to have constitutional protection, with its rules principles dictated for the Great Letter, generating consequences in the field of the Inheritance law. The work consists of demonstrating to the importance of the element AFFECTION as family former, going beyond the rules daily pay-established for the current text of Civil Code and giving a new treatment to the basic principles that guide the blood relations, with affectively related sights to assure the successory right to.